2009
DOI: 10.1055/s-0029-1210674
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and Post-Calcium Load Serum Calcium, Parathyroid Hormone, Calcitonin, in Male Idiopathic Calcium Urolithiasis - Evidence for a Basic Disturbance in Calcium Metabolism

Abstract: In male healthy controls (n = 12), male renal calcium stone patients with either normocalciuria (NC; n = 12) or idiopathic hypercalciuria (I-HC; n = 12), all ideally matched for age and body weight, the response of variables of mineral metabolism to a calcium-rich oral test meal was evaluated. In all groups the postprandial urinary cyclic AMP is decreased as compared with fasting urine, indicating that the parathyroid glands are suppressible by oral calcium. However, in I-HC serum total calcium was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Differences in filtered load of calcium between IHSF and N and between fasting and fed conditions do not account for the observed changes in urine calcium excretion. Others, using single semisynthetic meal preparations with a large added calcium load (27), found prompt urine calcium increases with modest changes in blood calcium, compatible with our findings. Oral calcium loads without foods and large amounts of high-calcium foods (15,17,27,28) produce only modest increases in blood calcium, but in none of these studies was tubule reabsorption measured.…”
Section: Eating Normal Foods Reduces Calcium Reabsorption More In Ihsupporting
confidence: 92%
See 2 more Smart Citations
“…Differences in filtered load of calcium between IHSF and N and between fasting and fed conditions do not account for the observed changes in urine calcium excretion. Others, using single semisynthetic meal preparations with a large added calcium load (27), found prompt urine calcium increases with modest changes in blood calcium, compatible with our findings. Oral calcium loads without foods and large amounts of high-calcium foods (15,17,27,28) produce only modest increases in blood calcium, but in none of these studies was tubule reabsorption measured.…”
Section: Eating Normal Foods Reduces Calcium Reabsorption More In Ihsupporting
confidence: 92%
“…Others, using single semisynthetic meal preparations with a large added calcium load (27), found prompt urine calcium increases with modest changes in blood calcium, compatible with our findings. Oral calcium loads without foods and large amounts of high-calcium foods (15,17,27,28) produce only modest increases in blood calcium, but in none of these studies was tubule reabsorption measured. In two studies of fasting IHSF and normal controls, tubule reabsorption of IH patients was slightly lower, as we found here (11,23).…”
Section: Eating Normal Foods Reduces Calcium Reabsorption More In Ihsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies have shown that patients with IH have an increased fasting fractional excretion of calcium, and many have fasting hypercalciuria, suggesting a role for decreased tubule calcium reabsorption [26]. Alternatively, the increased absorption of calcium with meals in IH could lead to a post-absorptive rise in blood calcium that increases the filtered load; this has been seen in studies using single high calcium foods or calcium alone [27]. Speculatively, PTH could be suppressed as well, which would decrease tubule calcium reabsorption.…”
Section: Renal Mineral Handling In Ihmentioning
confidence: 99%